Pasantía En Ingeniería Civil En El Área De Licitaciones De La Empresa Arco Constructores S.A.S (2022)
This degree work is presented for the development of the internship in the company ARCO CONSTRUCTORES S.A.S. as a degree project, where we find the activities related to the civil engineer in the bidding area, which are: monitoring the contractual process, analyzing and calculating budgets, presenting the offer. The activities were carried out under the supervision of the Civil Engineer, legal representative of the company ARCO CONSTRUCTORES S.A.S. to correctly support the bidding processes, where feedback is generated for each activity carried out, and thus be able to efficiently support the activities necessary for the bidding procedure.